KOSAKATA DALAM WACANA ALAT PERAGA KAMPANYE PEMILU 2019 (Vocabulary in Discourse 2019 Election Campaign Props) - Endro Nugroho Wasono Aji; Agus Sudono; NFN Sutarsih; Rini Esti Utami (Kandai, 2022)
In the election campaign, legislative candidates often spread political promises to achieve their goals by using words that seem bombastic. This can easily be found in campaign demontration tools in the form of billboards, banners, or posters hanging on the side of the road. This study aims to reveal the phenomenon of vocabulary use in the 2019 Election campaign by using critical discourse analysis. Critical discourse analysis according to Fairclough is divided into three stages, namely description, interpretation, and explanation. The text descriptions contained in the 2019 Election campaign discourse are limited to vocabulary use only. The vocabulary aspects used are in the form of classification patterns, words that are fought for ideologically, the use of metaphors, and meaning relations. At the interpretation stage, the caleg uses vocabulary to form a positive image which in the end is expected to increase the electability of the caleg. At the explanatory stage, at the socio-cultural level, the efforts made by candidates are to build emotional closeness to the public (especially people who have the right to vote). This is done by utilizing lingual features, such as: the use of our personal pronouns, metaphors, and the use of regional languages (Javanese). Dalam kampanye pemilu para calon legislatif seringkali menebar janji-janji politik untuk mencapai tujuan mereka dengan memanfaatkan kata-kata yang terkesan bombastis. Hal tersebut dengan mudah dapat dijumpai dalam alat peraga kampanye yang berupa baliho, spanduk, atau poster yang terpampang di pinggir jalan. Penelitian ini bertujuan mengungkap fenomena penggunaan kosakata dalam kampanye Pemilu 2019 dengan menggunakan analisis wacana kritis. Analisis wacana kritis menurut Fairclough dibagi dalam tiga tahap, yaitu deskripsi, interpretasi, dan eksplanasi. Deskripsi teks yang terdapat dalam wacana  kampanye Pemilu 2019 dibatasi hanya pada penggunaan kosakata. Aspek kosakata yang digunakan berupa pola klasifikasi, kata-kata yang diperjuangkan secara ideologis, penggunaan metafora, dan relasi makna. Pada tahap interpretasi caleg memanfaatkan kosakata untuk membentuk citra positif yang pada akhirnya diharapkan dapat meningkatkan elektabilitas si caleg. Pada tahap eksplanasi, pada tataran sosiokultural upaya yang dilakukan oleh caleg adalah membangun kedekatan secara emosional dengan khalayak (masyarakat), terutama yang mempunyai hak pilih. Hal tersebut dilakukan dengan memanfaatkan fitur-fitur lingual, seperti penggunaan pronominal persona kita, metafora, dan penggunaan bahasa daerah (bahasa Jawa).